The Use Of Internet As A Retail Medium In Malaysia - Norlaila, Abdullah @ Abdul Hamid (2001)

(untitled)
The objective of this study is to find out the use of the lnternet as a retail medium in Malaysia. A total of 150 retailer's companies were chosen from their Web site on the lnternet and they were interviewed by using electronic-mail questionnaire. Generally, the respondents showed positive perspective of the lnternet as a retail medium in Malaysia. The Computer and IT sector is the biggest user of the lnternet in Malaysia, but the usage is still at the early stage. The preferred criterion for lnternet evaluation and approval into business is the capability of the lnternet to support business activities. The currently usage of Web server among retailers in Malaysia is to publicize the company information. The most common lnternet application used among retailers is the use of electronic mail. lnternet is expected to enhance the sources of knowledge. And they also believed other companies succeed because of lnternet applications. Even though the lnternet is promising the bright prospect in business, the security of the lnternet is still vague to it users. From the regression analysis, it showed that the size of employee in a firm, the type of firm, the number of employee with lnternet access and duration of practicing lnternet in the company did not influenced the use of lnternet as a retail medium in Malaysia.